2022
DOI: 10.3389/fgene.2021.812456
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Heterozygosity and Genome-Wide Analysis of Heterozygosity Regions in Two Duroc Pig Populations

Abstract: Heterozygosity can effectively reflect the diverse models of population structure and demographic history. However, the genomic distribution of heterozygotes and the correlation between regions of heterozygosity (runs of heterozygosity, ROHet) and phenotypes are largely understudied in livestock. The objective of this study was to identify ROHet in the Duroc pig genome, and investigate the relationships between ROHet and eight important economic traits. Here, we genotyped 3,770 American Duroc (S21) and 2,096 C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…Several heterozygosity islands harboured genes previously reported in association with immune response, rather than with healthrelated QTL. Duroc and Large White shared the ROHet island on SSC2 (91.8-93.63 Mb), which was reported as ROH island by Schiavo, Bovo, Bertolini, et al (2020) in Calabrese breed and partially overlapped the ROHet island detected in a Duroc sample (Ruan et al, 2022). This island harbours the EDIL3, an immune-related gene that was reported 3 times upregulated in umbilical-herniaaffected Landrace pigs (Souza et al, 2020).…”
Section: Roh and Rohet Islandsmentioning
confidence: 73%
See 2 more Smart Citations
“…Several heterozygosity islands harboured genes previously reported in association with immune response, rather than with healthrelated QTL. Duroc and Large White shared the ROHet island on SSC2 (91.8-93.63 Mb), which was reported as ROH island by Schiavo, Bovo, Bertolini, et al (2020) in Calabrese breed and partially overlapped the ROHet island detected in a Duroc sample (Ruan et al, 2022). This island harbours the EDIL3, an immune-related gene that was reported 3 times upregulated in umbilical-herniaaffected Landrace pigs (Souza et al, 2020).…”
Section: Roh and Rohet Islandsmentioning
confidence: 73%
“…Finally, Cinta Senese, Casertana, Mora Romagnola, and cosmopolitan breeds outlined ROHet islands on SSC2, SSC6, SSC14, and SSC15 that mapped genes and QTL linked to productive traits (Howard et al, 2015;Kim et al, 2021;Li et al, 2011;Qi et al, 2022;Zappaterra et al, 2021;Zhang et al, 2015). In particular, the heterozygosity-rich segment, observed on SSC6 (54.2-55.9 Mb) in Duroc, Landrace, Large White, and Pietrain, correlates with QTL for average daily gain, daily feed intake, fat androstenone level, mean corpuscular haemoglobin concentration and meat colour, and partially overlapped a ROHet island detected by Ruan et al (2022) in a Duroc sample.…”
Section: Roh and Rohet Islandsmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, Meyermans et al [33] has shown that MAF and LD pruning severely impact ROH analyses and recommend to avoid MAF and LD pruning prior to ROH analyses based on medium density genotypes. Meanwhile, ROHet has far less characterized than ROH in livestock, especially in pigs [16] , [60] . Biscarini et al [57] presented the results of the first sensitivity analysis for ROHet and varied the number of missing and homozygous SNPs allowed inside ROHet.…”
Section: Discussionmentioning
confidence: 99%
“…The variant rs346331089 located in the intron of SPATA6 , which is one of sperm-specific genes. Previous studies suggested the regulation of the expression pattern of SPATA6 linked to spermatogenesis in Hu sheep [ 45 ] and inactivation of SPATA6 leaded to acephalic spermatozoa and male sterility in mice [ 46 ]. These results above manifested high-intensity directional selection on certain economic traits might influenced the number of teats in pigs.…”
Section: Discussionmentioning
confidence: 99%